A tool to assess the feasibility of VOIP for contact centres - Venter, Anton (Department of Computer Science, 2024)
With Voice-over-Internet-Protocol 1 (VO IP), voice calls travel over the same network as data, potentially making the voice network redundant and thereby reducing an organisation's investment in network infrastructure and its support and administration costs. Since voice is the primary communication medium for customer servicing, other benefits could potentially be realized when VOIP is applied in contact centres. However the feasibility of VOIP depends on many factors and makes the evaluation of its feasibility a complex issue. This research proposes an assessment tool to evaluate the feasibility of VOIP in the contact centre(s) of a business, given the current and intended characteristics of the contact, centre and its technology infrastructure. Execution of the assessment requires input from an individual familiar with the current contact centre and its basic technology infrastructure, rather than VOIP itself From past implementations of VOiP and literature available, this research identifies the relevant factors that influence the feasibility of VOIP. These are used to formulate questions that make up a questionnaire. The answers to the questionnaire are applied to a calculation to produce an overall rating of the feasibility of VOIP for the organisation's particular situation. The assessment tool was implemented as a web-based interactive application, which interrogates a user by way of the questionnaire and immediately gives a "score" indicating the feasibility of VOiP as a new technology. The resulting tool also indicates which factors made a considerable negative contribution towards VOIP not being feasible for the particular organisation.